2016
DOI: 10.1155/2016/1313027
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Investigation of Complement Pathway Genes in Type 2 Diabetic Retinopathy: An Inflammatory Perspective

Abstract: Diabetic retinopathy (DR) has complex multifactorial pathogenesis. This study aimed to investigate the association of complement pathway genes with susceptibility to DR. Eight haplotype-tagging SNPs of SERPING1 and C5 were genotyped in 570 subjects with type 2 diabetes: 295 DR patients (138 nonproliferative DR [NPDR] and 157 proliferative DR [PDR]) and 275 diabetic controls. Among the six C5 SNPs, a marginal association was first detected between rs17611 and total DR patients (P = 0.009, OR = 0.53 for recessiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Single-nucleotide polymorphisms in complement genes are associated with a number of retinal diseases, including glaucoma (Scheetz et al, 2013), age-related macular degeneration (AMD) (Weber et al, 2014), and diabetic retinopathy (Yang et al, 2016; Wang et al, 2013). The immune-privileged retina is among others under regular immune surveillance by proteins of the complement system.…”
Section: Introductionmentioning
confidence: 99%
“…Single-nucleotide polymorphisms in complement genes are associated with a number of retinal diseases, including glaucoma (Scheetz et al, 2013), age-related macular degeneration (AMD) (Weber et al, 2014), and diabetic retinopathy (Yang et al, 2016; Wang et al, 2013). The immune-privileged retina is among others under regular immune surveillance by proteins of the complement system.…”
Section: Introductionmentioning
confidence: 99%
“…One study found the intronic SNP rs2269067 in the C5 gene to be associated with proliferative diabetic retinopathy in the Chinese Han population, and this SNP was shown to be associated with increased C5 mRNA expression [ 20 ]: the study also noted an increase in the production if IL-6 associated with the rs2269067 SNP. Another study found a weak association between the coding SNP rs17611 (which results in the V802I polymorphism in the C5 protein previously associated with rheumatoid arthritis [ 23 ]) and diabetic retinopathy in type 2 diabetes [ 24 ]. Given the data linking diabetic retinopathy to complement over-activation, it has been suggested that anti-complement therapeutics have potential for treating diabetic retinopathy [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…2016a; Yang et al. 2016a). Complement factors B (CFB ) is a competitor of CFH and both regulate the activation of the complement alternative pathway (Wang et al.…”
Section: Chronic Hyperglycaemiamentioning
confidence: 99%
“…Yang et al. (2016a) analysed six polymorphisms (rs12237774, rs2269066, rs17611, rs1548782, rs10985126 and rs1017119) in the gene encoding C5 in their Chinese cohort. They found that two of the SNPs were associated with DR (rs17611 and rs1548782).…”
Section: Chronic Hyperglycaemiamentioning
confidence: 99%